Formation of a radical tricationic tetraborane(4) by hydride abstraction from sp3-sp3-hybridized diboranes - Litters, Sebastian; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2016)
The formation, electronic structure, and reactivity of the recently-reported radical tricationic tetraborane [B4(hpp)4]·3+ (hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate), which features a planar rhomboid B4 unit and bridging bicyclic guanidinate (hpp) substituents, is reported. New experiments show that the tetraborane could be synthesized by hydride abstraction either in a very fast reaction from the electron-rich sp3?sp3-hybridized diborane [HB(hpp)]2, or in a very slow reaction from the cationic, less electron-rich sp3?sp3-hybridized diborane [HB(hpp)2BPCy3]+. The results argue for an electron-transfer in the rate-determining step of a complex reaction sequence. Quantum chemical calculations highlight the role of the hpp substituents for the stabilization of the radical tricationic tetraborane [B4(hpp)4]·3+. Further analysis shows that [B4(hpp)4]·3+ is highly reactive, and especially a very strong electrophile. This reactivity makes the compound very interesting because boron atoms in such a low oxidation state (<2) are expected to be strong nucleophiles.
Im Titel ist die Zahl "3" jeweils hochgestellt
Gesehen am 27.05.2020